2020
DOI: 10.1002/ece3.6973
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and genetic evidence for four species of gentoo penguin

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
3
8
0
Order By: Relevance
“…The tracking data reported here suggest source populations for the ongoing range expansion of gentoo penguins in the WAP. Genetic analysis indicates that basin-scale dispersal and colonization events are rare for this species, and the Polar Front is an effective boundary between sub-Antarctic and Antarctic populations [ 23 , 43 ]. At smaller spatial scales, gentoo penguins are well-known colonizers of new breeding territory and quickly take advantage of ice-free breeding space [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tracking data reported here suggest source populations for the ongoing range expansion of gentoo penguins in the WAP. Genetic analysis indicates that basin-scale dispersal and colonization events are rare for this species, and the Polar Front is an effective boundary between sub-Antarctic and Antarctic populations [ 23 , 43 ]. At smaller spatial scales, gentoo penguins are well-known colonizers of new breeding territory and quickly take advantage of ice-free breeding space [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gentoo penguins (P. papua), on the other hand, exhibited greater genomic structure among colonies geographically isolated on different islands (15.81% and F ST =0.217). However, the analysis of gentoo penguins involved divergent lineages that were recently proposed to represent at least four distinct species, based on their genomic divergence and fine-scale morphometric differences (Clucas et al, 2018;de Dinechin et al, 2012;Pertierra et al, 2020;Tyler et al, 2020;Vianna et al, 2017). Another recent study using mitochondrial genomes from all penguin species found that the range of sequence divergence among well-defined species is 0.8%-5.2% (Cole, Dutoit, et al, 2019;Cole, Ksepka, et al, 2019).…”
Section: Gene Flow Among Rockhopper Taxamentioning
confidence: 99%
“…oceanographic conditions over their distributional range, diet and breeding period), it may constrain differentiation in some phenotypic traits (Fiser et al, 2018) if they have moved towards the same adaptive peak. The extent of niche overlap might also explain the limited morphological differentiation among Eudyptes penguins, not only for the rockhopper penguin, but also among other penguin species complexes (Tyler et al, 2020). In this sense, the use of genomic approaches with extensive sampling across the species complex range is critically important if inter-versus intraspecific taxonomic boundaries are to be delineated.…”
Section: Integrative Taxonomymentioning
confidence: 99%
“…Gentoo penguins Pygoscelis papua are distributed across the Falklands, subantarctic islands and Antarctic Peninsula, and the 25% of the world population that breeds at South Georgia (Lynch, 2013) has been proposed as a cryptic species P. poncetii (Tyler et al., 2020). Poor krill availability during winter at South Georgia can reduce gentoo penguin breeding numbers in the following breeding season by lowering survival and breeding propensity (Croxall & Rothery, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Gentoo penguins Pygoscelis papua are distributed across the Falklands, subantarctic islands and Antarctic Peninsula, and the 25% of the world population that breeds at South Georgia (Lynch, 2013) has been proposed as a cryptic species P. poncetii (Tyler et al, 2020).…”
Section: Introductionmentioning
confidence: 99%